ADOPSI CHATGPT DALAM KOMUNIKASI AKADEMIK MAHASISWA: ANALISIS TECHNOLOGY ACCEPTANCE MODEL - Devi Rantika; Rendra Widyatama (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Recent advances in artificial intelligence technology have significantly increased the use of ChatGPT within digital learning systems in higher education. This study aims to investigate the factors influencing students’ acceptance of ChatGPT by applying the Technology Acceptance Model (TAM) framework, as well as examining whether differences in acceptance exist based on academic background. A quantitative survey approach was employed involving 115 active students from Ahmad Dahlan University representing the Faculty of Industrial Technology and the Faculty of Literature, Culture, and Communication who had prior experience using ChatGPT. Data were collected through questionnaires and analyzed using descriptive statistics, validity and reliability testing, linear regression analysis, and independent sample t-tests. The findings revealed that perceived ease of use positively affected perceived usefulness, while perceived usefulness emerged as the strongest predictor shaping students’ attitudes toward the use of ChatGPT. Furthermore, students’ attitudes toward ChatGPT were found to positively influence their intention to continue utilizing the platform in digital learning activities. The study also identified no significant differences in ChatGPT acceptance between students from the two faculties. These findings indicate that ChatGPT has evolved into an integral component of the digital learning ecosystem across academic disciplines rather than being limited to specific fields of study. This research contributes practical insights for educational institutions in understanding the factors that support the integration of generative AI technologies into students’ learning processes. ABSTRAK Inovasi dalam teknologi kecerdasan buatan telah membawa peningkatan penggunaan ChatGPT pada sistem pembelajaran digital di perguruan tinggi. Penelitian ini bertujuan menelaah faktor-faktor yang memengaruhi penerimaan mahasiswa terhadap ChatGPT menggunakan pendekatan Technology Acceptance Model (TAM), serta menguji adanya perbedaan penerimaan ditinjau dari latar belakang akademik. Metode survei dengan pendekatan kuantitatif digunakan dalam penelitian ini dengan melibatkan 115 mahasiswa aktif Universitas Ahmad Dahlan dari dua fakultas, yaitu Fakultas Teknologi Industri dan Fakultas Sastra, Budaya, dan Komunikasi, yang telah menggunakan ChatGPT. Data diperoleh melalui kuesioner dan dianalisis menggunakan teknik statistik deskriptif, pengujian validitas, reliabilitas, regresi linear, serta independent sample t-test. Hasil analisis memperlihatkan bahwa persepsi kemudahan penggunaan memengaruhi persepsi manfaat, dan persepsi manfaat menjadi faktor dominan dalam membentuk sikap penggunaan ChatGPT. Selain itu, sikap penggunaan terbukti berpengaruh positif terhadap niat mahasiswa untuk terus memanfaatkan ChatGPT dalam aktivitas pembelajaran digital. Penelitian ini juga menemukan bahwa tidak terdapat perbedaan signifikan tingkat penerimaan ChatGPT antara mahasiswa dari kedua fakultas. Temuan tersebut menunjukkan bahwa penggunaan ChatGPT telah berkembang sebagai bagian dari ekosistem pembelajaran digital lintas disiplin di perguruan tinggi dan tidak terbatas pada bidang akademik tertentu. Penelitian ini memberikan kontribusi praktis dalam memperkuat pemahaman institusi pendidikan mengenai faktor-faktor yang mendukung integrasi teknologi AI generatif dalam proses pembelajaran mahasiswa.